Efficacy and safety of protein C concentrate to treat purpura fulminans and thromboembolic events in severe congenital protein C deficiency - Manco-Johnson, Marilyn J.; Bomgaars, Lisa; Palascak, Joseph; Shapiro, Amy; Geil, John; Fritsch, Sandor; Pavlova, Borislava G.; Gelmont, David (Thrombosis and Haemostasis, 2016)
Severe congenital protein C (PC) deficiency (SCPCD) is associated with disseminated intravascular coagulation (DIC), purpura fulminans (PF), and vascular thromboembolic events (TE), often leading to organ failure and death. PC replacement therapy offers a safe, effective treatment for thromboembolic complications of SCPCD and secondary prophylaxis for recurrent DIC, PF, and TEs. A prospective, multi-centre, open-label, phase 2/3 study was conducted to demonstrate the safety and efficacy of protein C concentrate for treatment of PF and acute TEs. Fifteen enrolled patients with SCPCD received protein C concentrate; 11 received treatment for acute TEs (PF, 18 events; PF and other coumarin-related vascular thromboembolic events [coumarin-induced skin necrosis; CISN], 1 event; venous thrombosis, 5 events). Predefined efficacy criteria for treatment of acute TEs were compared with a historical control arm (i. e. patients receiving conventional therapy without protein C replacement). PF/CISN was demonstrated by pre-defined primary and secondary efficacy ratings. Primary ratings of protein C concentrate–treated episodes were significantly higher (p=0.0032) than in the historical control. For 19 PF/CISN episodes in 11 patients, 94.7 % of treatments were rated effective and 5.3 % effective with complications (not related to protein C concentrate). In a secondary efficacy rating, all treatments were rated effective (68.4 % excellent; 21.1 % good; 10.5 % fair). For 5/24 vascular thrombosis episodes, 80 % of treatments were rated excellent and 20 % were rated good. No treatment-related adverse events or serious adverse events occurred. In conclusion, protein C concentrate provides an efficacious, safe treatment for PF, CISN, and other TEs in SCPCD patients.
Keywords: Disseminated intravascular coagulation; protein C deficiency; congenital thrombotic disease due to protein C deficiency; purpura fulminans; therapeutics